Eksistensi Gereja dalam Sejarah Keselamatan : Perspektif Sistematik terhadap Peran dan Panggilan Eklesia - Yurniwati Waruwu; Abad Jaya Zega (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the existence of the Church in the context of salvation history from the perspective of systematic theology, focusing on the role and vocation of the ecclesia as the community of God's people. The background of this study departs from the belief that the Church is not just a religious institution, but has an existential and historical basis in God's saving work. The Church acts as an extension of Christ's mission which is continued in the power of the Holy Spirit. In this research, the author uses a qualitative method with a literature study approach. The data sources consist of the Holy Bible, theological books related to the title, as well as relevant theological journal articles. This research was conducted to understand the relationship between the Church's identity and its participation in salvation history, both dogmatically and functionally. The results show that the Church is called to be an active witness in the work of salvation, by carrying out prophetic, liturgical, and social functions. As an ecclesia, the Church is not just a collection of individual believers, but a community that lives in relationship with Christ as the Head. The discussion emphasizes that the Church has a mandate to live in unity, holiness, catholicity, and apostolate, all of which are rooted in God's grace. In conclusion, the existence of the Church in salvation history is eschatological and missionary. The Church is called to be a sign and means of salvation, and to take part in the salvation of the world.